Guided Bone Regeneration: Descriptive and Retrospective Study Between PRF Membranes and PTFE-e. - Barros Guedes, Erik Vinicius; Melo Figueira, Mariana Maia; Gonçalves Figueira, Luis Carlos; Viana de Jesus, Oliver Renê; Ercilia de Araújo, Maria (Brazilian Journal of Implantology and Health Sciences, 2024)
After the dental extraction and removal of lesions, the reabsorption of the alveolar bone crest of the area is common and inevitable, which can lead to a dimensional change of the bone area in terms of thickness and height. To regenerate the lost bony amount, and to make possible the placement of implants with predictability, checking restoration of function and aesthetics, the Guided Bone Regeneration (GBR) is often necessary. The GBR consists of a surgical procedure in which membrane barriers are used, with or without bone grafts. It is based on the concept of osteopromotion, which includes the use of physical means (barriers) to promote a total sealing of a certain anatomical area, preventing external agents and mainly connective tissue from interfering with the osteogenesis process. This barrier is positioned in close contact with the resorbed bone, isolating the periosteum in the external part of the membrane. Nowadays in commerce, countless materials can be used as a barrier in GBR, however, the purpose of this study is to describe the effects of the PRF membranes and PTFE-e membranes, observing the characteristics of each and its properties through literature and scientific studies, being able to conclude its positive and negative effects on its actions on bony regeneration can be concluded.